Influence of spacing on the initial production of hedgerow "Arbequina" olive orchards - Leon, L.=700 1 De la Rosa, R.; Rallo, L.; Guerrero, N.; Barranco, D.
Es, En)
Ilus., 17 ref.
Keywords: OLEA EUROPAEA; ESPACIAMIENTO; RECOLECCION; ESPAÑA